Do 1, 8-naphthyridine sulfonamides possess an inhibitory action against Tet(K) and MsrA efflux pumps in multiresistant Staphylococcus aureus strains?. (October 2020) - Oliveira-Tintino, Cícera Datiane de Morais; Tintino, Saulo Relison; Muniz, Débora Feitosa; Barbosa, Cristina Rodrigues dos Santos; Pereira, Raimundo Luiz Silva; Begnini, Iêda Maria; Rebelo, Ricardo Andrade; da Silva, Luiz Everson; Mireski, Sandro Lucio; Nasato, Michele Caroline; Lacowicz Krautler, Maria Isabel; Pereira, Pedro Silvino; et al.
Abstract: Naphthyridines represent a class of heterocyclic compounds formed by two condensed aromatic rings. This study aimed to evaluate the antibacterial activity and in vitro inhibition of efflux resistance mechanisms of a series of 1, 8-naphthyridine sulfonamides against strains carrying Tet(K) and MsrA efflux pumps. The efflux pump inhibitory capacity was evaluated by analyzing synergistic effects between 1, 8-naphthyridine sulfonamides and standard antibiotics, as well as ethidium bromide. The following 1, 8-naphthyridines were used: 4-methyl-N-(5-chloro-1, 8-naphthyridin-2-yl)-benzenesulfonamide (Naph 1); 2, 5-Dichloro-N-(5-chloro-1, 8-naphthyridin-2-yl)-benzenesulfonamide (Naph 2); 2, 3, 4-trifluoro-N-(5-chloro-1, 8-naphthyridin-2-yl)benzenesulfonamide (Naph 7); 3-trifluoromethyl-N-(5-chloro-1, 8-naphthyridin-2-yl)-benzenesulfonamide (Naph 9). The 1, 8-naphthyridine sulfonamide derivatives possessed a potential Tet(K) and MsrA efflux pump inhibitory action. Graphical abstract: Image 1